Gambaran Kejadian Dermatitis Kontak Akibat Kerja pada Petugas Cleaning Service di RSUP Prof. Dr. R. D. Kandou Manado - Paendong, Ristya; Pandaleke, Herry; Mawu, Ferra (e-CliniC, 2017)
Abstract: Work-related diseases that cause skin disorders are called occupational skin diseases inter alia contact dermatitis and urticaria. Work-related contact dermatitis reaches 20% of all occupational diseases; 80% of them occur in hands. Occupational contact dermatitis can be experienced by all workers such as cleaning service workers because they are often exposed to irritants and allergen substances in their work places due to unavailable personal protective equipment. This study was aimed to obtain the overview of occupational contact dermatitis incidence among cleaning services of Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive study with a cross sectional design. Respondents of this study involved 135 cleaning service workers obtained by using total sampling method. The results showed that 28 of 135 respondents (20,7%) were suffered from occupational contact dermatitis. Conclusion: Occupational contact dermatitis was found in around 20% of the cleaning service workers at Prof. Dr. R. D. Kandou Hospital Manado.Keywords: occupational contact dermatitis, cleaning serviceÂ Abstrak: Penyakit akibat kerja yang menyebabkan kelainan pada kulit disebut penyakit kulit akibat kerja yang dapat berupa dermatitis kontak dan urtikaria. Dermatitis kontak akibat kerja (DKAK) mencapai 20% dari seluruh penyakit akibat kerja dan 80% terjadi di tangan. Dermatitis kontak akibat kerja dapat terjadi pada semua pekerja, diantaranya petugas cleaning service akibat sering terpapar bahan iritan dan alergen di tempat kerja tanpa penggunaan alat pelindung diri yang memadai dan tingkat kebersihan diri yang buruk. Penelitian ini bertujuan untuk mengetahui gambaran kejadian DKAK pada petugas cleaning service di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ini ialah deskriptif dengan desain potong lintang. Jumlah responden penelitian sebanyak 135 orang diperoleh dengan teknik total sampling. Hasil penelitian menujukkan bahwa 28 dari 135 responden (20,7%) mengalami dermatitis kontak akibat kerja. Simpulan: Dermatitis kontak akibat kerja ditemukan pada sekitar 20% petugas cleaning service RSUP Prof. Dr. R. D. Kandou Manado.Kata kunci: dermatitis kontak akibat kerja, cleaning service